Change Management and Organizational Effectiveness of Culinary SMEs in Greater Bandung: Mediating Role of Value Creation - Arief Ramdhany; Hari Mulyadi; Imas Purnamasari (Al-Muraqabah: Journal of Management and Sharia Business, 2022)
Abstract This paper examines the effect of change management on value creation and organizational effectiveness of Culinary SMEs in Greater Bandung moderated by firm age. We utilized a quantitative approach and a descriptive survey method by questionnaire to get the data from the café owners as respondents. The population (and also the sample) was 98 café owners of the SMEs in culinary sector. Data were collected through questionnaire and analyzed using Partial Least Square (PLS) and regression analysis with PROCESS Procedure to measure mediation and moderation effects. The findings of this research are that value creation and organizational effectiveness are strongly influenced by change management. Value creation can function as mediating variable for the relationship between change management and organizational effectiveness. The variable of firm age has a moderation effect on the influence of change management on organizational effectiveness, but do not have moderation effect on the influence of value creation on organizational effectiveness. Keywords: change management, organizational effectiveness, value creation, culinary SMEs